Teacher-student rapport in a middle school classroom in China : a dialogic perspective / Wang Xiao Yi - Wang, Xiao Yi (2013)
China‘s New Curriculum Reform emphasizes the need for students to be active participants in the teaching-learning process, which requires reciprocal dialogue. Reciprocal dialogue is the avenue through which teacher-student rapport is built. Furthermore, it is the building of such rapport which serves as the basis for the student‘s active cooperation and participation in the teaching-learning process. This study presents the findings of a basic qualitative study which discusses the classroom, which serves as the basis for analyzing classroom dialogue in order to explore to what extent the teacher-student rapport which is advocated by China‘s New Curriculum Reform is being implemented in the classroom. This study is furthermore supported by Buber‘s dialogic theory of building an ―I – Thou‖ relationship between teacher and student. The research sample comprised the classes of three teachers from a Chinese government school which is a model school for implementing China‘s New Curriculum Reform. Each of the three classes consisted of middle school students between the ages of 13 and 15. Classroom dialogue was recorded and transcribed, and coded as well. Furthermore, the school principal, teachers and students were interviewed in order to receive feedback on their understanding of teacher-student rapport. Through analyzing the data of classroom dialogue and interviews with the school principal, teachers and students, it was apparent that teacher-student rapport was affected by many factors, and implementing teacher-student rapport as advocated by China‘s New Curriculum Reform is a long-term process, whereby teachers themselves will need more ―hands on‖ experiences regarding building teacher-student rapport.